Empirical investigation on energy dependence-consumption nexus: Evidence from Turkish natural gas market - (:unkn) unknown (ELSEVIER SCI LTD, 2014)
Because energy dependence is an important issue for today's energy markets, understanding its effect on the long-term relationships in the markets has crucial implications. We argue that dependence strongly affects the interaction between energy consumption and its determinants even if this market is regulated. To test this hypothesis, this paper empirically investigates the long-term dynamics among the related variables in the Turkish natural gas market, because the market is under regulation and Turkey is an energy dependence country in natural gas. The aim is to understand the effect of dependence on the long-term dynamics of natural gas consumption in Turkey. To this aim, we employ a simultaneous co-integration model with structural breaks. Our findings suggest that energy dependence strongly affects the long-term dynamics of gas consumption. Also, we find that governments intervene in price regulated by an independent regulator. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Energy dependence; Regulation; Elasticity; Co-integration; Structural breaks; UNIT-ROOT; PRICE ELASTICITIES; DEMAND